Clinical Trial Studies of Antipsychotics during Symptomatic Presentations of Agitation and/or Psychosis in Alzheimer’s Dementia: A Systematic Review - Haider Qasim; Maree Donna Simpson; Jennifer L. Cox (Psychiatry International, 2023)
Aggressive behaviors of people with dementia pose a significant challenge to employees in nursing homes and aged care facilities. Aggressive behavior is a result of psychomotor agitation in dementia (BPSD). Globally, psychotropic interventions are the preferred treatment for BPSD. However, it is still unclear which psychotropic should be prescribed. The purpose of this systematic review is to compare pharmacological interventions for psychomotor agitation and psychosis symptoms. Method: The studies were extracted from databases, such as PubMed, OVID, and Cochrane, with a date restriction from 2000 to present, and in English. PRISMA steps were used to refine the extracted data. The RCTs extracted for this systematic review compared active ingredient medications to one another or to a placebo. Results: PRISMA was used to assess all selected trials comprehensively. Four trials are being conducted on quetiapine, two on haloperidol, one on olanzapine, three on risperidone, one on brexpiprazole, one on pimavanserin, and two on aripiprazole. Compared to typical antipsychotics, quetiapine showed tolerable adverse effects and did not worsen parkinsonism. Psychosis symptoms and behavioral improvements can be improved with haloperidol. Among elderly patients with psychosis, risperidone reduces angriness, paranoia, and aggression, as well as improves global functioning. As compared with other antipsychotics, aripiprazole provides a lower risk of adverse effects and demonstrated improvement in agitation, anxiety, and depression associated with psychosis. While olanzapine improves hostile suspiciousness, hallucinations, aggression, mistrust, and uncooperativeness, it worsens depression symptoms. Psychosis was treated effectively with pimavanserin without adverse effects on motor functions. Psychosis symptoms are well tolerated by brexpiprazole, but insomnia, headache, and urinary tract infections are common side effects. Conclusions: In this systematic review, we provide an overview of how to choose the correct antipsychotics and dosages for the management of BPSD and emphasize the importance of safe and conservative use of these drugs.